Surgery Is Not Superior to Dilation for the Management of Vaginal Agenesis in Mayer-Rokitansky-Küster-Hauser Syndrome: A Multicenter Comparative Observational Study in 131 Patients. Issue 2 (February 2019) - Cheikhelard, Alaa; Bidet, Maud; Baptiste, Amandine; Viaud, Magali; Fagot, Christine; Khen-Dunlop, Naziha; Louis-Sylvestre, Christine; Sarnacki, Sabine; Touraine, Philippe; Elie, Caroline; Aigrain, Yves; Polak, Michel
Abstract : (Abstracted from Am J Obstet Gynecol 2018;219:281.e1–281.e9) Mayer-Rokitansky-Küster-Hauser (MRKH) syndrome is a rare congenital condition characterized by vaginal agenesis, which impairs sexuality and has a negative impact on quality of life (QOL). Classic management of this condition is to create a cavity allowing satisfying painless penetrative intercourse.